COMPARATIVE MARKET ANALYSIS OF WORLD PRODUCTION AND INTERNATIONAL FRUIT TRADING - Đorović, Milutin; Milanović, Milan; Stevanović, Simo (Economics of Agriculture, 2009)
This paper contains a regional-comparative analysis of some of the most important indicators of the world production and international trading in fruit, as extremely significant in the diet and indispensable food product group. It specially analyses trends, concerning regional differences in the volume, dynamics and structure of production and trade of apples, plums, cherries and sour cherries, strawberries, raspberries and grapes. Regions, i.e. countries, the largest producers and largest exporters and importers of these products have been defined. Subsequently, it was found that there are very significant regional differences which is the consequence of numerous natural, economic and social factors. In the analysis of character of relations and the degree of influence of aformentioned factors on changes and development directions of the observed phenomenon, quantitative and qualitative market research methods were used.